RISK FACTORS ANALYSIS OF DIABETIC FOOT ULCERS AMONG INDIVIDUAL WITH DIABETES MELLITUS - Eko Prabowo (UPT Penerbitan Universitas Jember, 2017)
Background: Diabetic foot ulcers are becoming a major health problem worldwide. And patients with diabetic foot ulcers are on the rise, ulcers are chronic and difficult to heal, infections and limb ischemia with the risk of amputation and even life-threatening. As well as these cases require substantial health resources, then providing a socio-economic burden for patients, communities, and countries. Method: This research is a Case Control Study, to determine the effect of risk factors on the occurrence of diabetic foot ulcers. The sampling technique used is concecutive sampling. The sample of this study consisted of 60 respondents, treatment group of 30 respondents that is diabetic foot ulcer patient and control group of 30 respondents, that is diabetic mellitus patient without diabetic foot ulcers. The instruments used were questionnaires and observation sheets. Bivariate analysis technique used Chi Square test (X²) and multivariate analysis using multiple logistic regression. Results: The results of this research indicate that the variable blood pressure has an OR value of 8.887 with p value of 0.031. In conclusion among the five independent variables, blood pressure variables had the most dominant effect on diabetic foot occurrence in Diabetes Mellitus patients at Genteng and Blambangan Hospitals. Conclusions: Patient with Diabetes Mellitus faced a high blood pressure problem, so they have a greater risk of complication. The compication is diabetic foot ulcer. So the patients is recommended to control his health to decrease the incidence of the diabetic foot ulcers Keywords: Diabetes Mellitus, Diabetic Foot Ulcer